The Effect Analysis of Thermal Efficiency and Optimal Design for Boiler System. (May 2017) - Chao, Luo; Ke, Luo; Yongzhen, Wang; Zhitong, Ma; Yulie, Gong
Abstract: The paper presents the effect of exhaust gas and inlet air temperature on thermal efficiency for boiler system. Based on the numerical model, the performance indexes of boiler system are calculated at different conditions using EES (Engineering Equation Software). The results show that when the exhausted gas or inlet air temperature increases 10-15°C, the heat loss of exhaust gas decreases 0.8%-1% and thermal efficiency of boiler system increases 0.8%-1%; The crucial factors that can affect thermal efficiency are exhaust gas temperature and fuel volatile ratio; seven optimized schemes are designed for a case of boiler system. A new methodology is provided for evaluating the efficiency of boiler system.